2012
DOI: 10.1039/c2cp41544e
|View full text |Cite
|
Sign up to set email alerts
|

Stability-improved organic n-channel thin-film transistors with nm-thin hydrophobic polymer-coated high-k dielectrics

Abstract: We report on the fabrication of N,N'-ditridecyl-perylene-3,4:9,10-tetracarboxylic diimide-C13 (PTCDI-C13), n-channel organic thin-film transistors (OTFTs) with 30 nm Al(2)O(3) whose surface has been un-modified or modified with hexamethyldisilazane (HMDS) and thin hydrophobic CYTOP. Among all the devices, the OTFTs with CYTOP-modified dielectrics exhibit the most superior device performance and stability. The optimum post-annealing temperature for organic n-channels on CYTOP was also found to be as low as 80 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Then, a 50 nm‐thin Al 2 O 3 film was deposited by atomic layer deposition (ALD) at 200 °C, followed by spin‐coating of diluted CYTOP (Ashai glass. Co.) solution on the Al 2 O 3 film; the spin‐coated CYTOP was post‐annealed at 180 °C in ambient oven . Then 60 nm‐thin heptazole channel layer (width/length = 500/90 μm) was patterned on the CYTOP/Al 2 O 3 double layer by organic molecule beam deposition (OMBD) system as we synthesized and imported the heptazole small‐molecule from our co‐workers (Luminano Co).…”
Section: Methodsmentioning
confidence: 99%
“…Then, a 50 nm‐thin Al 2 O 3 film was deposited by atomic layer deposition (ALD) at 200 °C, followed by spin‐coating of diluted CYTOP (Ashai glass. Co.) solution on the Al 2 O 3 film; the spin‐coated CYTOP was post‐annealed at 180 °C in ambient oven . Then 60 nm‐thin heptazole channel layer (width/length = 500/90 μm) was patterned on the CYTOP/Al 2 O 3 double layer by organic molecule beam deposition (OMBD) system as we synthesized and imported the heptazole small‐molecule from our co‐workers (Luminano Co).…”
Section: Methodsmentioning
confidence: 99%
“…Park et al [95] have shown that by using a bilayer structure of CYTOP/Al 2 O 3 the threshold voltage shift can be minimized. They fabricated and tested an n-channel OTFT based on N ,N -ditridecylperylene-3,4,9,10-tetracarboxylic diimide (PTCDI-C13).…”
Section: High-k/low-k Bilayer-based Otftsmentioning
confidence: 99%
“…To further improve the turn-on characteristics, there has been a focus on thin and high-κ dielectric layers to increase the gate capacitance, leading to a lower subthreshold swing. [16][17][18][19][20][21] In this study, we focus on the subthreshold regime from a microscopic perspective, especially its relation to the trap DOS. Single-crystal OFET measurements with extremely low subthreshold swing are presented, and the theoretical description of the subthreshold current to extract the trap DOS is summarized.…”
Section: Introductionmentioning
confidence: 99%